Flow cytometry lyophilised-reagent tube for quantifying peripheral blood neutrophil myeloperoxidase expression in myelodysplastic syndromes (MPO-MDS-Develop): protocol for a diagnostic accuracy study. Issue 10 (7th October 2022) - Raskovalova, Tatiana; Scheffen, Laura; Jacob, Marie-Christine; Chevalier, Simon; Tondeur, Sylvie; Bulabois, Bénédicte; Meunier, Mathieu; Szymanski, Gautier; Lefebvre, Christine; Planta, Charlotte; Dumestre-Perard, Chantal; Gonnet, Nicolas; et al.
Abstract : Introduction: Suspicion of myelodysplastic syndromes (MDS) is the most common reason for bone marrow aspirate in elderly patients. Peripheral blood neutrophil myeloperoxidase expression quantified by flow cytometric analysis might rule out MDS for up to 35% of patients referred for suspected disease, without requiring bone marrow aspiration. Yet laboratory-developed liquid antibody cocktails have practical limitations, because of lack of standardisation and poor stability. This research project aims to estimate the level of agreement and comparative accuracy between a single-use flow cytometry tube of lyophilised reagents (BD Lyotube Stain 468) and its laboratory-developed liquid reagent counterpart in quantifying peripheral blood neutrophil myeloperoxidase expression, among adult patients referred for suspected MDS. Methods and analysis: The MPO-MDS-Develop project is a cross-sectional diagnostic accuracy study of two index tests by comparison with a reference standard in consecutive unselected adult patients conducted at a single university hospital. Flow cytometry analysis of peripheral blood samples will be performed by independent operators blinded to the reference diagnosis, using either Lyotube Stain 468 or laboratory-developed liquid reagent cocktail. The reference diagnosis of MDS will be established by cytomorphological evaluation of bone marrow aspirate by two independent haematopathologists blinded to the index test results. Morphologic assessment will be complemented by bone marrow flow cytometric score, karyotype and targeted next-generation sequencing panel of 43 genes, where relevant. The target sample size is 103 patients. Ethics and dissemination: An institutional review board (Comité de Protection des Personnes Sud Est III, Lyon, France) approved the protocol prior to study initiation (reference number: 2020-028-B). Participants will be recruited using an opt-out approach. Efforts will be made to release the primary results within 6 months of study completion. Trial registration number: NCT04399018 .